Raising children : surprising insights from other cultures - Lancy, David F. (2017)
An intriguing, sometimes shocking, journey across the world to show how children are raised in different cultures. -- Provided by publisher.
Why in some parts of the world do parents rarely play with their babies and never with toddlers? Why in some cultures are children not fully recognized as individuals until they are older? How are routine habits of etiquette and hygiene taught--or not--to children in other societies? Drawing on a lifetime's experience as an anthropologist, David F. Lancy takes us on a journey across the globe to show how children are raised differently in different cultures. Intriguing, and sometimes shocking, his discoveries demonstrate that our ideas about children are recent, untested, and often contrast starkly with those in other parts of the world. Lancy argues that we are, by historical standards, guilty of over-parenting, of micro-managing our children's lives. Challenging many of our accepted truths, his book will encourage parents to think differently about children, and by doing so to feel more relaxed about their own parenting skills. -- Provided by publisher.
Introduction : leave the kids alone -- Culture and infancy -- Questions about infant attachment -- Children playing and learning -- Protection versus suppression -- Going to school -- The consequences of raising "unique individuals" -- Summary and speculation -- The backstory.
Includes bibliographical references (pages 171-202) and index.
Keywords: Child rearing -- Cross-cultural studies; Parenting -- Cross-cultural studies; Child rearing; Parenting; Cross-cultural studies